(untitled) (The Research of Medical Science Review, 2025)
Multiple drug-resistant tuberculosis (MDR-TB) is difficult to treat, especially when it develops along with other illnesses. The study focuses on how patients with MDR-TB are also affected by different health conditions and necessitates proper care. Objectives:To determine the prevalence and types of comorbidities in patients diagnosed with MDR-TB. To assess the impact of these comorbidities on treatment duration, adverse drug reactions, and clinical outcomes. Study Desgin: A Observational Retrospective Cohort Study. Place and Duration of study: From 01 November 2024 to 30 April 2025 Pulmonology Department, Fatima Jinnah Institute of Chest Diseases, Quetta. Methods 150 patients diagnosed with MDR-TB from a tuberculosis treatment center. Evidence of comorbid conditions was found by accessing clinical documents and performing tests. CPSP approved the study’s ethical requirements (Ref No CPSP/REU/PUL-2022-001-740). Results 40% of participating patients had a comorbid condition. Out of all cases, the most common was diabetes mellitus (25%), followed by HIV infection (10%) and chronic obstructive pulmonary disease (5%). Those who had comorbidities took longer to be treated and experienced more bad side effects from the medicines. Conclusion Precisely because many MDR-TB patients have multiple health problems, their overall treatment results are often negative. In MDR-TB programs, screening should be thorough and the involvement of different doctors is recommended.